Evaluation of potential mechanisms for skeletal muscle mass recovery early after left ventricular assist device implantation - Didjana Celkupa, BS; Benjamin A. Sweigart, MA; Joronia Chery, BA; Alex Coston, MD; Laura Telfer, BS MS; Matthew Lawrence, BS; Michael S. Kiernan, MD MS; Gregory S. Couper, MD; Masashi Kawabori, MD; Nathan LeBrasseur, PhD MS; Edward Saltzman, MD; Amanda R. Vest, MBBS MPH (JHLT Open, 2025)
Background: We observed significant gains in appendicular lean mass (ALM) over the first 6 months of left ventricular assist device (LVAD) support for patients with heart failure with reduced ejection fraction (HFrEF). We sought to determine whether improved HF neurohumoral stability, inflammation, physical activity, or nutrition, are most closely related to this muscle mass recovery. Methods: We prospectively recruited 30 adults with HFrEF ±21 days from LVAD implantation. Dual X-ray absorptiometry (DXA) measured ALM at baseline and at 3- and 6-months post-LVAD implantation (n = 22 with ALM at baseline and 3 months). Markers of neurohumoral HF stability (NT-proBNP, growth differentiation factor-15), inflammation [high sensitivity C-reactive protein (hsCRP)], habitual physical activity (24-hour average steps), and nutritional intake (24-hour average dietary protein) were also recorded. Mixed effects models separately evaluated the change in each parameter over time and relationships with the change in ALM. Results: At baseline, participants (87% male, mean age 56 ± 12 years) showed a significant negative association between ALM and log N-terminal-pro B natriuretic peptide (NT-proBNP) (r = −0.38, 95% CI −0.66, −0.001, p = 0.050) and log growth differentiation factor-15 (GDF-15) (r = −0.42, 95% CI −0.69, −0.05, p = 0.027). Over the 6-month study period, NT-proBNP and hsCRP decreased, 24-hour steps increased, whereas GDF-15 and 24-hour dietary protein were unchanged. There was an increase in ALM across study timepoints, which was significantly associated only with reductions in log NT-proBNP and hsCRP on mixed effects models. Conclusions: The recovery in ALM over the first 6 months of LVAD support was most closely associated with improved HF neurohumoral stability and inflammation, rather than activity or nutritional changes.